Gestão social no Conselho Estadual de Defesa dos Direitos Humanos no Tocantins - Panda, Aires Paulo Pedro (Universidade Federal do Tocantins, 2019)
The participation of organized civil society in the public sphere has advanced with new proposals and innovative models of development and this dissertation deals precisely with this participation when it analyzes social management in the State Council for the Defense of Human Rights (CEDDH-TO), discusses the functioning of the Council, identifies the characteristics of social management as well as addresses participation in the Council. Date collection was qualitative in nature. Field research was carried out through participant observation at Council meetings, semi-structured interviews, questionnaire application and meeting minutes analysis. A study was carried out between May 24, 2016 and November 27, 2018. The results indicate that the Council is not able to interfere in the allocation of public funds, and that the most discussed issues at the meetings are the Statute of the Rights of the Child , Adolescents and Elders and the approval of the State Human Rights Plan. There is a potential of CEDDH-TO for social management, as well as the need for improvement in all aspects so that the experience can strengthen the Council and consolidate it in the public sphere as an adequate space for social management.